Perceptions and support of the Muslim community towards the development of marine halal tourism - Chairani, Nur; Hidayaturrahman, Mohammad (Journal of Halal Science and Research, 2025)
Halal Tourism is a culture-based tourism that prioritizes Islamic Principles and Sharia and hopes to build a superior moral personality as its foundation. The research used a qualitative descriptive method to develop marine halal tourism in Indonesia, especially on the island of Madura. Problem-solving methods used interviews, observations, documentation, and literature studies that refer to the Muslim community's perception of marine halal tourism in Indonesia. The results of this evaluation show that by cooperating with the Government of the Tourism Office, the community and other parties in the perception and support of the Muslim community to develop Marine Halal Tourism on the island of Madura and explore the potential of local areas to increase tourist visitor satisfaction to enjoy facility services by Islamic Sharia. In this case, Halal Maritime Tourism can provide positive things for the Muslim community, especially on Madura Island, so that they can maintain their culture and customs to maintain honor, and foreign tourists can also appreciate the local culture on Madura Island.   Keywords: Halal tourism, Maritime tourism, Muslim tourism.